STRATEGI PENGOPTIMALAN MEDIA SOSIAL DALAM MENINGKATKAN PENJUALAN DITINJAU DARI MANAJEMEN PEMASARAN SYARIAH (Studi Kasus pada Home Industry “Djampi Desa” Kecamatan Bungah) - Dinda Roudhotun Ni'mah; Nur Fadhillah; Muhammad Shaiful Umam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of digital technology has encouraged business actors to utilize social media as an effective and efficient medium for marketing, sales, and communication without requiring substantial costs. This study aims to determine the social media optimization strategy, examine the implementation of Islamic marketing management principles in social media optimization, and identify the supporting and inhibiting factors of social media optimization in increasing the sales of Djampi Desa in Bungah District. This study employed a qualitative approach with a phenomenological research design. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that Djampi Desa's social media optimization strategy is implemented through content concept planning, the preparation of promotional materials, and the determination of posting schedules and publication times. In its implementation, Djampi Desa utilizes various social media platforms, including WhatsApp, Instagram, Facebook, and TikTok. From the perspective of sharia marketing management, Djampi Desa's marketing practices have reflected the principles of shiddiq, amanah, fathanah, and tabligh, through the delivery of honest, clear, and transparent information, understanding consumer needs in accordance with market demand, and building consumer trust. Nevertheless, the completeness of product information still needs to be improved to ensure that consumers receive clearer information. The supporting factors include the availability of technology, ease of interaction, and the popularity of social media. Meanwhile, the inhibiting factors include limited technological understanding, limited human resources, and time constraints.